Programme theories to describe how different general practitioner service models work in different contexts in or alongside emergency departments (GP-ED): realist evaluation - Bridie Evans (Emergency Medicine Journal, 2024)
Background Addressing increasing patient demand and improving ED patient flow is a key ambition for NHS England. Delivering general practitioner (GP) services in or alongside EDs (GP-ED) was advocated in 2017 for this reason, supported by £100 million (US$130 million) of capital funding. Current evidence shows no overall improvement in addressing demand and reducing waiting times, but considerable variation in how different service models operate, subject to local context.Methods We conducted mixed-methods analysis using inductive and deductive approaches for qualitative (observations, interviews) and quantitative data (time series analyses of attendances, reattendances, hospital admissions, length of stay) based on previous research using a purposive sample of 13 GP-ED service models (3 inside-integrated, 4 inside-parallel service, 3 outside-onsite and 3 with no GPs) in England and Wales. We used realist methodology to understand the relationship between contexts, mechanisms and outcomes to develop programme theories about how and why different GP-ED service models work.Results GP-ED service models are complex, with variation in scope and scale of the service, influenced by individual, departmental and external factors. Quantitative data were of variable quality: overall, no reduction in attendances and waiting times, a mixed picture for hospital admissions and length of hospital stay. Our programme theories describe how the GP-ED service models operate: inside the ED, integrated with patient flow and general ED demand, with a wider GP role than usual primary care; outside the ED, addressing primary care demand with an experienced streaming nurse facilitating the ‘right patients’ are streamed to the GP; or within the ED as a parallel service with most variability in the level of integration and GP role.Conclusion GP-ED services are complex . Our programme theories inform recommendations on how services could be modified in particular contexts to address local demand, or whether alternative healthcare services should be considered.